007.6 Role of minority stress in health-risk behaviours among young msm and tgs in india. (13th September 2015) - Satpathy, Maheswar
Abstract : Introduction: Literature shows MSM and TGs face exorbitant levels of minority stress. Moreover, health-risk behaviours in young MSM and TG have not been comprehensively studied in all parts of India. Therefore, an insight into the potential role of minority stress in mental health of young MSM and TGs, and further health-risk behaviours is essential. The study explored the pathways and mechanisms of engagement in health risk behaviours among young MSM and TGs using minority stress perspective. Methods: A mixed method approach (Qual-Quant-Qual) was adopted to examine how minority stress predicts poor mental health, and the role of mental health as a mediator variable in health-risk behaviours. 6 FGDs of 5 participants each were followed by a focused questionnaire development building on the insights from the FGDs. After field pilot, collection of Quant Data from 220 young MSM and TGs (18–30 years), using TSS was performed. In-depth Interviews on a focused and smaller yet representative sample of 32 was conducted. Results: This study establishes that components and associates of minority stress (internalised homophobia, perceived and actual discrimination, gender non-conformity stigma, non-acceptance of sexual/social identity, experiences of violence and impact of criminalization of Homosexuality) significantly predict poor mental health outcomes among young MSM and TGs (e.g. anxiety and depression). This establishes Meyer's Minority stress perspective and its cross-cultural validity in Indian context for the first time. This study also significantly suggests role of mental health as mediator variable in influencing health-risk behaviours including sexual risk-taking and alcohol and drug abuse. Conclusion: Health-risk behaviours are a byproduct of the interaction between socio-cultural contexts, person's social and community identity, sexual identity acceptance by self and others (e.g. criminalization in Indian context). Insights of the study will inform policy makers to assess LGBT rights and health policies and create increased sensitivity in the mainstream society. Disclosure of interest statement: This study was funded by AusAID as an Australian Leadership Award Scholarship to the Researcher. No pharmaceutical or other grants were received in the development of this study.